2014
DOI: 10.1002/path.4368
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific and age‐dependent effects of global Mdm2 loss

Abstract: Mdm2, an E3 ubiquitin ligase, negatively regulates the tumor suppressor p53. In this study, we utilized a conditional Mdm2 allele, Mdm2FM, and a CreER Tamoxifen inducible recombination system to examine the effects of global Mdm2 loss in adult mice. Two different Tamoxifen injection regimens caused 100% lethality of Mdm2FM/−;CreER mice. Both radio-sensitive and radio-insensitive tissues were impaired. Strikingly, a large number of radio-insensitive tissues, including the kidney, liver, heart, retina and hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 39 publications
6
41
1
Order By: Relevance
“…The p53ER TAM mouse model showed that in the absence of MDM2, p53 is spontaneously activated and induces apoptosis in radio-sensitive organs (Ringshausen et al 2006). Somatic knockout of MDM2 also causes apoptosis in both radio-sensitive and radio-insensitive tissues, resulting in organ damage and rapid death (Zhang et al 2014). Clinical trials of MDM2 inhibitor RG7112 encountered toxicities consistent with the effects of p53 activation in the hematopoietic system, suggesting that the observations in mice may also be applicable to humans (Ray-Coquard et al 2012).…”
Section: Therapeutic Induction Of P53 Apoptosis and Arrest Functionsmentioning
confidence: 86%
“…The p53ER TAM mouse model showed that in the absence of MDM2, p53 is spontaneously activated and induces apoptosis in radio-sensitive organs (Ringshausen et al 2006). Somatic knockout of MDM2 also causes apoptosis in both radio-sensitive and radio-insensitive tissues, resulting in organ damage and rapid death (Zhang et al 2014). Clinical trials of MDM2 inhibitor RG7112 encountered toxicities consistent with the effects of p53 activation in the hematopoietic system, suggesting that the observations in mice may also be applicable to humans (Ray-Coquard et al 2012).…”
Section: Therapeutic Induction Of P53 Apoptosis and Arrest Functionsmentioning
confidence: 86%
“…While p53 is readily stabilized in radiosensitive tissues and some nonradiosensitive tissues , in other organs such as the liver, no changes in its levels are observed. In addition, p53 stability/activity is dampened in older mice (Feng et al 2007;Zhang et al 2014). This implies that temporal and tissue-specific factors might be involved in regulating p53 levels.…”
Section: Why Do Multiple Enzymes Inhibit P53 Functions?mentioning
confidence: 92%
“…It is overly simplistic to assume that a ubiquitously expressed multifunctional protein like p53, which is so intricately involved in determining cell fate, could be regulated by a single/universal E3 ligase in multicellular organisms. Effects of p53 stabilization are also manifested in different ways depending on tissue type and developmental stage (Ringshausen et al 2006;Zhang et al 2014). While p53 is readily stabilized in radiosensitive tissues and some nonradiosensitive tissues , in other organs such as the liver, no changes in its levels are observed.…”
Section: Why Do Multiple Enzymes Inhibit P53 Functions?mentioning
confidence: 99%
“…Again, whether autophagy restrains p53 activity or whether this neurodegeneration is p53 dependent is not known and will be interesting to test. Augmented p53 activity does underlie some brain abnormalities, neurologic dysfunction, and neurodegeneration (Trimmer et al 1996; Morrison et al 2003; Bae et al 2005; Terzian et al 2007; Checler and Alves da Costa 2014; Zhang et al 2014), raising the possibility that restraining p53 by autophagy in this setting may be important to prevent tissue damage and organismal death.…”
Section: Autophagy Suppresses P53mentioning
confidence: 99%